Measuring intergenerational energy justice: Building an index - Rodrigues Carlos Henrique; Leme Le-Lyne Paes; Bermejo Paulo Henrique (E3S Web of Conferences, 2025)
Energy justice refers to the global energy system that equitably distributes the benefits and costs of energy services. The configuration of energy systems must incorporate the dimension of generational justice, so that future generations are not burdened with obsolete infrastructures unable to provide even basic services. From the gap on the incorporation of generational justice as dimensions of energy justice, this study developed a framework of metrics based on the SDGs and used the Our World in Data database, thus building an index for measuring generational justice. The index was applied to countries that are part of two blocs: G7 and BRICS. The results show that the G7 countries perform better, but there are large differences between blocs and countries and that their historical and geographical attributes and the direction of their public policies directly influence intergenerational energy justice.